Intestinal Parasitic Infestation in School Going Children of Rishikesh, Uttarakhand, India - Bansal, Deepankar; Gupta, Pratima; Singh, Gagandeep; Bhatia, Mohit; Singla, Harshit (Indian Journal of Community Health, 2018)
Background: Intestinal parasitism(IP) remains a common problem in school going children. Aims & Objectives: To study the prevalence IP infestation in school going children and to study the relation with type of water supply and sanitation. Material and Methods: A cross sectional study was carried out and a total of 461 stool samples were collected from children under ten years of age from various schools of Rishikesh. The normal saline and iodine mounts of fresh and saturated salt solution concentrated samples were examined. Modified Ziehl Neelsen staining was done for detection of coccidian parasites. The statistical significance within gender, age, drinking water supply, sanitation and other socio-demographic parameters was assessed by Chi-square test. Results: 112 (24.3%) out of 461 were positive for intestinal parasites. Giardia lamblia was the commonest parasite (15.2%) followed by Hymenolepis nana (2.38%), Hookworm (2.17%), Enterobius vermicularis (2.17%), Entamoeba histolytica (2.17%), Ascaris lumbricoides (0.86%), and Cryptosporidium parvum (0.86%). Conclusions: Due to lack of proper sanitation & education along with low socioeconomic background, IP infections are still prevalent among school children. Regular awareness program on promoting good health, maintenance of proper personal hygiene and carrying out regular deworming in schools should be instituted for control.